PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA MENGGUNAKAN PENDEKATAN KETERAMPILAN PROSES DI KELAS V SDN 10 SUNGAI LIMAU KAB. PDG. PARIAMAN - Anggreani, Elvira; Astimar, Nelly; Zuryanty, Zuryanty (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
ABSTRACT The purpose of the research was to describe the improvement of student learning outcomes in Civics learning with the Process Skill Approach in the fifth grade of SDN 10 Sungai Limau, Padang Pariaman Regency. This type of research is Class Action Research using a qualitative and quantitative approach with procedures for planning, implementing, observing, and reflecting. The research instruments were in the form of observation sheets and items. Conducted in Semester II of 2017/2018 Academic Year. The research subjects were teachers as observers, researchers as practitioners, and fifth grade students as many as 15 students. The results of the first cycle of research on lesson plans averaged 80.35% (good), increased in the second cycle to 93% (very good). The implementation of the first cycle on the teacher aspect averaged 79.25% (enough), increased in the second cycle to 95.83% (very good). Implementation of the first cycle on the aspect of students on average 71% (sufficient), increased in the second cycle to 91.67% (very good). Student learning outcomes in the first cycle averaged 74 (enough), increased in the second cycle to 85 (good). It can be concluded the Skill Approach The process shows that it can improve student learning outcomes in science learning in schools Basic.Keywords: Process Skills Approach, Learning Outcomes